A modified low-temperature high-toughness PPR pipe and its preparation process

By preparing and combining nucleating agent components, combined with EVA composite VTES grafted EPDM and acrylic grafted HDPE, the PPR pipe was modified, and the problem of insufficient brittleness and toughness at low temperatures was solved, significantly improving physical strength and low temperature impact resistance.

CN119752049APending Publication Date: 2025-04-04JIANGXI CHENSHI TECH GRP CO LTD

Patent Information

Application Number
CN202510060137.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing PPR materials are brittle and prone to cracking at low temperatures, resulting in their impact performance and toughness under low temperature conditions that cannot meet the practical application requirements.

Method used

By preparing nucleating agent components A and B and combining them, a composite β nucleating agent is formed, combined with EVA composite VTES grafted EPDM and acrylic grafted HDPE, the PPR tube is modified to improve its low-temperature impact resistance.

Benefits of technology

It significantly improves the physical strength and low-temperature toughness of PPR pipes, reduces the volume change of the material when the temperature changes, reduces the thermal expansion coefficient, and enables the pipes to work normally at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752049A_ABST
    Figure CN119752049A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer materials, and specifically to a modified low-temperature high-toughness PPR pipe and a preparation process thereof. The preparation process comprises the following steps: preparing a nucleating agent component A; preparing a nucleating agent component B; preparing a compounded β nucleating agent; preparing an EVA composite VTES grafted EPDM; and preparing a low-temperature high-toughness PPR pipe. The present invention compounds a compounded nucleating agent, a nucleating agent component A prepared with phthalic anhydride as the main material, and a nucleating agent component B prepared with lanthanum oxide as the main material, so that component A and component B act synergistically, refine the grains, and the fine and uniform crystal structure helps to improve the elastic modulus and rigidity of the pipe. At the same time, a more dense and uniform crystal structure can reduce the volume change of the material when the temperature changes, thereby reducing the thermal expansion coefficient, so that the pipe can work normally at low temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a modified low-temperature high-toughness PPR pipe and a preparation process thereof. Background Art

[0002] Random polypropylene (PPR) is widely used in industrial applications such as pipes, packaging bags, automotive parts, and furniture due to its excellent flexibility, corrosion resistance, high temperature and high pressure resistance, and long service life. However, PPR is particularly brittle at low temperatures and is prone to cracking. The impact resistance and toughness of PPR pipes at low temperatures fall far short of practical application requirements, significantly impacting their transportation and use in autumn and winter or in cold regions. Therefore, effectively improving the cold resistance of PPR and reducing its low-temperature brittleness are key technical challenges that need to be addressed.

[0003] Currently, existing technologies address the problem of PPR's insufficient low-temperature toughness and prone to cracking by adding polymer elastomers, nucleating agents, or toughening agents. For example, Patent CN104592644B uses a masterbatch of a low-temperature cracking modifier and a masterbatch of a crystal form modifier to improve the low-temperature impact resistance of PPR materials. However, 20% of the pipes still cracked in a low-temperature drop hammer test at 0°C, 1.5kg, and 1.5m. Patent CN113061304B proposes a strategy for synergistically improving the low-temperature toughness of PPR pipes by using ethylene-propylene block copolymers, a β-nucleating agent, and linear low-density polyethylene. Although this significantly improves the low-temperature impact resistance of the pipes, the pipes require a long aging process, and unaged pipes exhibit poor low-temperature cracking resistance. Therefore, the present invention provides a modified low-temperature, high-toughness PPR pipe and its preparation process, further enhancing the pipe's physical strength and low-temperature toughness. Summary of the Invention

[0004] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a modified low-temperature high-toughness PPR pipe and a preparation process thereof.

[0005] A preparation process for a modified low-temperature high-toughness PPR pipe comprises the following steps:

[0006] S1: Preparation of nucleating agent component A

[0007] Dissolving phthalic anhydride in THF to obtain a phthalic anhydride THF solution, dissolving an aliphatic diamine in THF to obtain an aliphatic diamine THF solution, and adding the aliphatic diamine THF solution dropwise to the phthalic anhydride THF solution to react and obtain a nucleating agent component A;

[0008] S2: Preparation of nucleating agent component B

[0009] Weighing lanthanum oxide and dissolving it in hydrochloric acid to obtain chloride crystals, dissolving the chloride crystals in ethanol to obtain a chloride ethanol solution, then adding stearic acid to the chloride ethanol solution to react to obtain a rare earth complex, mixing alcohol with distilled water, and then adding calcium carbonate to obtain a calcium salt solution, and reacting the calcium salt solution, citric acid solution, and rare earth complex to prepare nucleating agent component B;

[0010] S3: Preparation of compound β nucleating agent

[0011] The nucleating agent component A and the nucleating agent component B are compounded in a volume ratio of 1:(2-3) to obtain a compounded β-nucleating agent;

[0012] S4: Preparation of EVA composite VTES grafted EPDM

[0013] EPDM latex is added to a reaction flask, followed by VTES and an initiator BPO to obtain VTES-grafted EPDM. EVA is placed in the reaction flask, followed by DCP and acetone. After sufficient stirring, the acetone is removed, and the VTES-grafted EPDM is added to prepare a molten mixture. The molten mixture is purified to obtain EVA composite VTES-grafted EPDM.

[0014] S5: Preparation of low temperature and high toughness PPR pipes

[0015] Acrylic acid, HDPE and benzophenone are reacted and sodium persulfate is added, and melt extrusion is performed to obtain acrylic acid grafted HDPE. PPR special resin, acrylic acid grafted HDPE, EVA composite VTES grafted EPDM, compound β nucleating agent, silane coupling agent, initiator BPO and masterbatch are mixed and stirred, and the mixed raw materials are melt-extruded, cooled and shaped, and cut to a fixed length to obtain low-temperature and high-toughness PPR pipes.

[0016] Furthermore, step S1 of preparing the nucleating agent component A comprises the following steps:

[0017] S1.1: Add 0.022-0.045 parts by mass of phthalic anhydride to a reaction flask, then add 30-35 parts by volume of THF. Stir magnetically at room temperature for 30-40 minutes until the phthalic anhydride is completely dissolved to obtain a phthalic anhydride THF solution.

[0018] S1.2: Take 0.01-0.05 parts by mass of an aliphatic diamine and dissolve it in 20-30 parts by volume of THF to obtain an aliphatic diamine THF solution, and add the aliphatic diamine THF solution dropwise to the phthalic anhydride THF solution. The volume ratio of the aliphatic diamine THF solution to the phthalic anhydride THF solution is 3:1. After the addition is completed, the reaction is continued at room temperature for 24-26 hours, and the white precipitate is separated by centrifugation. The white precipitate is washed with THF 3-5 times, and the resulting product is vacuum dried at 60-80°C for 12-14 hours to obtain the nucleating agent component A.

[0019] Furthermore, step S2 is to prepare the nucleating agent component B, comprising the following steps:

[0020] S2.1: Weigh lanthanum oxide and dissolve it in 37 wt% hydrochloric acid at a material-to-liquid ratio of 1:(9-10). Heat in an oil bath at 90-100°C to obtain chloride crystals for later use.

[0021] S2.2: Dissolve the chloride crystals in ethanol at a solid-liquid ratio of chloride crystals to ethanol of 1:(5-6) g / L to obtain a chloride-ethanol solution. Add stearic acid to the chloride-ethanol solution and stir to mix uniformly. The volume ratio of the chloride-ethanol solution to stearic acid is 1:(3-5). Slowly add sodium hydroxide solution dropwise to adjust the pH to 8. The mixture is reacted in an oil bath at 85-95°C for 3-4 hours to obtain a rare earth complex.

[0022] S2.3: Mix ethanol and distilled water in a volume ratio of (3-5):1 and add to a reaction flask. Stir magnetically for 30-40 minutes. Then, add 10-15% of the total mass of calcium carbonate in the reaction flask and allow it to completely disperse in the solution to obtain a calcium salt solution.

[0023] S2.4: Slowly add citric acid solution to calcium salt solution at 80-90℃ and react for 30-40 minutes, then slowly add rare earth complex, the mass ratio of calcium salt solution, citric acid solution and rare earth complex is (10-15):2:5, until the solution reacts completely to obtain a white emulsion, dissolve it in alcohol under ultrasound until the white emulsion is completely dissolved, and finally dry it at 90-100℃ for 24-26 hours for use to obtain nucleating agent component B.

[0024] Furthermore, step S4 is to prepare EVA composite VTES grafted EPDM, comprising the following steps:

[0025] S4.1: Add 250-300 parts by weight of EPDM latex to a reaction flask and introduce nitrogen with stirring for 30 minutes. Heat the water bath to 68-72°C, add VTES and initiator BPO, and react under nitrogen for 6-8 hours. Rinse with distilled water, and then vacuum dry at 40-50°C for 24-26 hours to obtain VTES-grafted EPDM.

[0026] S4.2: Weigh 2-3 parts by weight of EVA into a reaction flask, add 1-1.5 parts by weight of DCP, and then add 3-4 parts by weight of acetone. Stir thoroughly until the materials in the reaction flask are evenly mixed. Place the mixture in a vacuum oven at room temperature to evacuate the acetone. After the acetone is completely evaporated, add 4-5 parts by weight of VTES-grafted EPDM. Add the mixture dropwise over 30 minutes and stir evenly.

[0027] S4.3: Pour the contents of the reaction flask into a HAKKEE torque rheometer and perform melt grafting for 10-15 minutes at 170-210°C and 60-80 rpm. Allow to cool to room temperature to obtain a molten mixture.

[0028] S4.4: Crush the molten mixture and add xylene. The material-liquid ratio of the molten mixture to xylene is 1:(25-30) g / mL. Stir at 60-80°C with the help of a magnetic stirrer until it is completely dissolved. While the solution is still hot, drop it into a room temperature reaction bottle containing methanol. Stir while it precipitates. Filter to obtain the precipitate. Dry the precipitate in a blast oven to obtain EVA composite VTES grafted EPDM.

[0029] Furthermore, step S5 prepares the low-temperature high-toughness PPR pipe, comprising the following steps:

[0030] S5.1: Acrylic acid, HDPE, and benzophenone are mixed in a mass ratio of (4-8):(6-10):(0.1-2), and the mixture is irradiated with a UV lamp at 80-90°C for 1-2 hours. After the UV lamp irradiation is completed, the mixture is allowed to stand at room temperature for 3-5 hours;

[0031] S5.2: After the standing, 0.1-2 parts of sodium persulfate are added to the acrylic acid and HDPE mixture, and the mixture is transferred to a twin-screw extruder for melt extrusion at 160-210°C, cooled, and pelletized to obtain acrylic acid-grafted HDPE;

[0032] S5.3: Place 80-90 parts by mass of PPR special resin, 2-4 parts by mass of acrylic grafted HDPE, 1-5 parts by mass of EVA composite VTES grafted EPDM, 0.1-2 parts by mass of compound β-nucleating agent, 1-3 parts by mass of silane coupling agent, 0.1-1 parts by mass of initiator BPO and 1-3 parts by mass of masterbatch into a blender and mix and stir for 10-15 minutes. Transfer the mixed raw materials to a twin-screw extruder for melt extrusion. After cooling, shaping and fixed-length cutting, low-temperature and high-toughness PPR pipes are obtained.

[0033] Furthermore, the melting temperature of the raw materials is 190-210°C, the mold temperature is 190-220°C, the extrusion temperature is 180-200°C, the screw speed is 300-450r / min, the feeding frequency is 5-10r / min, the first stage of cooling and shaping is vacuum cooling, the vacuum degree is less than -0.06MPa, the cooling temperature is 30-50°C, and the second stage of cooling and shaping is cooling under normal air pressure, and the cooling temperature is 15-25°C.

[0034] A modified low-temperature high-toughness PPR pipe is prepared by the above-mentioned preparation process of the modified low-temperature high-toughness PPR pipe.

[0035] Compared with the prior art, the present invention has at least the following beneficial effects:

[0036] 1. In the present invention, lanthanum oxide is loaded on calcium carbonate when preparing the nucleating agent component, and the mixture is compounded with stearic acid. The stability of the lanthanum oxide loaded on calcium carbonate is improved by modification with citric acid. Lanthanum oxide, as the main body of the nucleating agent, can provide nucleation sites. After the calcium carbonate particles are loaded with lanthanum oxide, the surface morphology of the calcium carbonate combined with lanthanum oxide changes, and the dispersibility is enhanced, thereby improving the dispersibility of the loaded system in the polymer matrix, reducing agglomeration, and making the crystal structure more uniform. After the calcium carbonate particles are loaded with lanthanum oxide, they are compounded with stearic acid. The stearic acid further changes the surface morphology of the loaded system, lubricates the surface of the calcium carbonate particles after being loaded with lanthanum oxide, and strengthens the interfacial bonding force between calcium carbonate and lanthanum oxide, further reducing the friction between the particles, and preventing agglomeration, thereby improving the rigidity and toughness of the pipe.

[0037] 2. The present invention compounds a nucleating agent by compounding a nucleating agent component A prepared with phthalic anhydride as the main ingredient and a nucleating agent component B prepared with lanthanum oxide as the main ingredient. The nucleating agent component A forms tiny crystal cores in the polymer melt, promoting the orderly arrangement of polymer molecular chains on its surface, thereby accelerating the crystallization process. The nucleating agent component B can form stable nucleation sites in the polymer melt, promoting the formation and growth of crystals. Components A and B act synergistically to provide nucleation sites at different stages, forming a multi-stage nucleation effect, thereby refining the grains and making the crystal structure more fine and uniform. The fine and uniform crystal structure helps to improve the elastic modulus and rigidity of the pipe. At the same time, the finer and more uniform crystal structure can reduce the volume change of the material when the temperature changes, thereby reducing the thermal expansion coefficient, so that the pipe can work normally at low temperatures.

[0038] 3. The acrylic acid grafted HDPE prepared by the present invention is obtained by primary grafting of acrylic acid and HDPE by ultraviolet light and secondary melt grafting and extrusion. The HDPE material has good strength and low-temperature impact resistance, and the high-density polyethylene molecular chains on the surface can react with free radicals generated by the decomposition of benzophenone under the irradiation of ultraviolet light to form active points, which further undergo polymerization reaction with acrylic acid monomers to form graft chains, thereby introducing polar groups into the surface of the non-polar HDPE material. During the melting process, acrylic acid and HDPE are further grafted under the initiation of additives, thereby introducing more strongly polar groups into the molecular chains of HDPE. The acrylic acid grafted HDPE with strong polar groups can effectively improve the compatibility with PPR materials and increase the interfacial bonding force with each component material, thereby giving full play to the characteristics of high strength and excellent low-temperature impact resistance of HDPE materials, thereby achieving the effect of increasing rigidity and toughness for PPR materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable one skilled in the relevant art to make and use the present disclosure.

[0040] Figure 1 The present invention provides a flow chart of the preparation process of a modified low-temperature high-toughness PPR pipe.

[0041] Figure 2 This is a scanning electron microscope (SEM) image of the impact cross section of the low-temperature, high-toughness PPR pipe of Example 1 of the present invention. DETAILED DESCRIPTION

[0042] The following describes in detail a modified low-temperature, high-toughness PPR pipe and its preparation process provided by the present invention, in conjunction with the accompanying drawings and specific embodiments. It is also noted that, to provide a more detailed description, the following embodiments are best and preferred embodiments, and those skilled in the art may employ alternative methods for implementing certain known technologies. Furthermore, the accompanying drawings are intended only to provide a more detailed description of the embodiments and are not intended to limit the present invention.

[0043] Example 1:

[0044] A preparation process for a modified low-temperature high-toughness PPR pipe, such as Figure 1 As shown, the following steps are included:

[0045] S1: Preparation of nucleating agent component A

[0046] S1.1: Add 0.022 parts by mass of phthalic anhydride to a reaction flask, then add 30 parts by volume of THF. Stir magnetically at room temperature for 30 minutes until the phthalic anhydride is completely dissolved to obtain a phthalic anhydride THF solution.

[0047] S1.2: Take 0.01 parts by mass of aliphatic diamine and dissolve it in 20 parts by volume of THF to obtain an aliphatic diamine THF solution, and add the aliphatic diamine THF solution dropwise to the phthalic anhydride THF solution. The volume ratio of the aliphatic diamine THF solution to the phthalic anhydride THF solution is 3:1. After the addition is completed, the reaction is continued at room temperature for 24 hours, and the white precipitate is separated by centrifugation. The white precipitate is washed with THF 5 times, and the resulting product is vacuum dried at 60°C for 12 hours to obtain the nucleating agent component A.

[0048] S2: Preparation of nucleating agent component B

[0049] S2.1: Weigh lanthanum oxide and dissolve it in 37 wt% hydrochloric acid at a material-to-liquid ratio of 1:10. Heat in an oil bath at 90°C to obtain chloride crystals for later use.

[0050] S2.2: Dissolve the chloride crystals in ethanol to obtain a chloride-ethanol solution. The solid-liquid ratio of the chloride crystals to ethanol is 1:5 g / L. Stearic acid is then added to the chloride-ethanol solution and stirred to mix uniformly. The volume ratio of the chloride-ethanol solution to stearic acid is 1:3. Sodium hydroxide solution is then slowly added dropwise to adjust the pH to 8. The mixture is reacted in an oil bath at 85°C for 3 h to obtain a rare earth complex.

[0051] S2.3: Mix ethanol and distilled water in a volume ratio of 3:1 and add to a reaction flask. Stir magnetically for 30 minutes. Then, add calcium carbonate (10% by weight of the total mass of the system) to the reaction flask and allow it to completely disperse in the solution to obtain a calcium salt solution.

[0052] S2.4: Slowly add citric acid solution to calcium salt solution at 80°C and react for 30 minutes, then slowly add rare earth complex. The mass ratio of calcium salt solution, citric acid solution and rare earth complex is 10:2:5. Continue until the solution reacts to obtain a white emulsion. Dissolve it in alcohol under ultrasound until the white emulsion is completely dissolved. Finally, dry it at 90°C for 24 hours for use to obtain nucleating agent component B.

[0053] S3: Preparation of compound β nucleating agent

[0054] The nucleating agent component A and the nucleating agent component B are compounded in a volume ratio of 1:3 to obtain a compounded β-nucleating agent.

[0055] S4: Preparation of EVA composite VTES grafted EPDM

[0056] S4.1: Add 250 parts by mass of EPDM latex to a reaction flask and introduce nitrogen with stirring for 30 minutes. Heat the water bath to 68°C, add VTES and initiator BPO, and react under nitrogen for 6 hours. Rinse with distilled water and then vacuum dry at 40°C for 24 hours to obtain VTES-grafted EPDM.

[0057] S4.2: Weigh 2 parts by mass of EVA into a reaction flask, add 1 part by mass of DCP, and then add 3 parts by mass of acetone. Stir thoroughly until the materials in the reaction flask are evenly mixed. Place the reaction flask in a vacuum oven at room temperature to evacuate the acetone. After the acetone is completely evaporated, add 4 parts by mass of VTES-grafted EPDM. Add the mixture dropwise over 30 minutes and stir until evenly mixed.

[0058] S4.3: The contents of the reaction flask were then poured into a HAKKEE torque rheometer and melt grafted at 170°C and 60 rpm for 10 min. The mixture was then allowed to cool to room temperature to obtain a molten mixture.

[0059] S4.4: Crush the molten mixture and add xylene with a material-liquid ratio of 1:25 g / mL. Stir at 60°C with the help of a magnetic stirrer until it is completely dissolved. While hot, drop the solution into a room temperature reaction bottle containing methanol. Stir while allowing it to precipitate, filter to obtain the precipitate, and dry the precipitate in a blast oven to obtain EVA composite VTES grafted EPDM.

[0060] S5: Preparation of low temperature and high toughness PPR pipes

[0061] S5.1: Acrylic acid, HDPE, and benzophenone were mixed in a mass ratio of 4:6:0.1. After mixing, the mixture was irradiated with a UV lamp at 80°C for 1 hour. After the UV lamp irradiation was completed, the mixture was allowed to stand at room temperature for 3 hours.

[0062] S5.2: After the standing, 0.1 part of sodium persulfate is added to the acrylic acid and HDPE mixture, and the mixture is transferred to a twin-screw extruder for melt extrusion at 160°C, cooled, and pelletized to obtain acrylic acid-grafted HDPE;

[0063] S5.3: 80 parts by mass of PPR special resin, 2 parts by mass of acrylic grafted HDPE, 1 part by mass of EVA composite VTES grafted EPDM, 0.1 parts by mass of compound β nucleating agent, 1 part by mass of silane coupling agent, 0.1 parts by mass of initiator BPO and 1 part by mass of masterbatch are put into a blender and mixed for 10 minutes. The mixed raw materials are transferred to a twin-screw extruder for melt extrusion. The melting temperature of the raw materials is 190°C, the mold temperature is 190°C, the extrusion temperature is 180°C, the screw speed is 300r / min, the feeding frequency is 5r / min, and then cooled and shaped. The first stage of cooling and shaping is vacuum cooling with a vacuum degree of less than -0.06MPa and a cooling temperature of 30°C. The second stage of cooling and shaping is cooling under normal air pressure with a cooling temperature of 15°C. After cutting to a fixed length, a low-temperature high-toughness PPR pipe is obtained. The impact cross-section scanning electron microscope image of the obtained low-temperature high-toughness PPR pipe is as follows Figure 2 shown.

[0064] Example 2:

[0065] A preparation process for a modified low-temperature high-toughness PPR pipe, such as Figure 1 As shown, the following steps are included:

[0066] S1: Preparation of nucleating agent component A

[0067] S1.1: Add 0.045 parts by mass of phthalic anhydride to a reaction flask, then add 35 parts by volume of THF. Stir magnetically at room temperature for 30 minutes until the phthalic anhydride is completely dissolved to obtain a phthalic anhydride THF solution.

[0068] S1.2: Take 0.05 parts by mass of aliphatic diamine and dissolve it in 30 parts by volume of THF to obtain an aliphatic diamine THF solution, and add the aliphatic diamine THF solution dropwise to the phthalic anhydride THF solution. The volume ratio of the aliphatic diamine THF solution to the phthalic anhydride THF solution is 3:1. After the addition is completed, the reaction is continued at room temperature for 24 hours, and the white precipitate is separated by centrifugation. The white precipitate is washed with THF 5 times, and the resulting product is vacuum dried at 60°C for 12 hours to obtain the nucleating agent component A.

[0069] S2: Preparation of nucleating agent component B

[0070] S2.1: Weigh lanthanum oxide and dissolve it in 37 wt% hydrochloric acid at a material-to-liquid ratio of 1:10. Heat in an oil bath at 90°C to obtain chloride crystals for later use.

[0071] S2.2: Dissolve the chloride crystals in ethanol to obtain a chloride-ethanol solution, wherein the solid-liquid ratio of the chloride crystals to ethanol is 1:5 g / L. Stearic acid is then added to the chloride-ethanol solution and stirred to mix uniformly, wherein the volume ratio of the chloride-ethanol solution to stearic acid is 1:5. Then, sodium hydroxide solution is slowly added dropwise to adjust the pH to 8. The mixture is reacted in an oil bath at 85°C for 3 h to obtain a rare earth complex.

[0072] S2.3: Mix ethanol and distilled water in a volume ratio of 5:1 and add to a reaction flask. Stir magnetically for 30 minutes. Then, add calcium carbonate (15% by weight of the total mass of the system) to the reaction flask and allow it to completely disperse in the solution to obtain a calcium salt solution.

[0073] S2.4: Slowly add citric acid solution to calcium salt solution at 80°C and react for 30 minutes, then slowly add rare earth complex. The mass ratio of calcium salt solution, citric acid solution and rare earth complex is 15:2:5. Continue until the solution reacts to obtain a white emulsion. Dissolve it in alcohol under ultrasound until the white emulsion is completely dissolved. Finally, dry it at 90°C for 24 hours for use to obtain nucleating agent component B.

[0074] S3: Preparation of compound β nucleating agent

[0075] The nucleating agent component A and the nucleating agent component B are compounded in a volume ratio of 1:2 to obtain a compounded β-nucleating agent.

[0076] S4: Preparation of EVA composite VTES grafted EPDM

[0077] S4.1: Add 300 parts by mass of EPDM latex to a reaction flask and introduce nitrogen with stirring for 30 minutes. Heat the water bath to 68°C, add VTES and initiator BPO, and react under nitrogen for 6 hours. Rinse with distilled water and then vacuum dry at 40°C for 24 hours to obtain VTES-grafted EPDM.

[0078] S4.2: Weigh 2 parts by mass of EVA into a reaction flask, add 1 part by mass of DCP, and then add 3-4 parts by mass of acetone. Stir thoroughly until the mixture is evenly mixed. Place the mixture in a vacuum oven at room temperature to remove the acetone. After the acetone has completely evaporated, add 4 parts by mass of VTES-grafted EPDM. Add the mixture dropwise over 30 minutes and stir thoroughly.

[0079] S4.3: The contents of the reaction flask were then poured into a HAKKEE torque rheometer and melt grafted at 170°C and 60 rpm for 10 min. The mixture was then allowed to cool to room temperature to obtain a molten mixture.

[0080] S4.4: Crush the molten mixture and add xylene. The material-liquid ratio of the molten mixture to xylene is 1:30 g / mL. Stir at 60°C with the help of a magnetic stirrer until it is completely dissolved. While hot, drop the solution into a room temperature reaction bottle containing methanol. Stir while it precipitates. Filter to obtain the precipitate. Dry the precipitate in a blast oven to obtain EVA composite VTES grafted EPDM.

[0081] S5: Preparation of low temperature and high toughness PPR pipes

[0082] S5.1: Acrylic acid, HDPE, and benzophenone were mixed in a mass ratio of 8:10:2. After mixing, the mixture was irradiated with a UV lamp at 80°C for 1 hour. After the UV lamp irradiation, the mixture was allowed to stand at room temperature for 3 hours.

[0083] S5.2: After the standing, 2 parts of sodium persulfate are added to the acrylic acid and HDPE mixture, and the mixture is transferred to a twin-screw extruder for melt extrusion at 160°C, cooled, and pelletized to obtain acrylic acid-grafted HDPE.

[0084] S5.3: Place 90 parts by mass of PPR special resin, 4 parts by mass of acrylic grafted HDPE, 5 parts by mass of EVA composite VTES grafted EPDM, 2 parts by mass of compound β-nucleating agent, 3 parts by mass of silane coupling agent, 1 part by mass of initiator BPO and 3 parts by mass of masterbatch into a blender and mix and stir for 10 minutes. Transfer the mixed raw materials to a twin-screw extruder for melt extrusion. The melting temperature of the raw materials is 190°C, the mold temperature is 190°C, the extrusion temperature is 180°C, the screw speed is 300r / min, the feeding frequency is 5r / min, and then cooled and shaped. The first stage of cooling and shaping is vacuum cooling with a vacuum degree of less than -0.06MPa and a cooling temperature of 30°C. The second stage of cooling and shaping is cooling under normal air pressure with a cooling temperature of 15°C. After cutting to a fixed length, a low-temperature and high-toughness PPR pipe is obtained.

[0085] Example 3:

[0086] A preparation process for a modified low-temperature high-toughness PPR pipe, such as Figure 1 As shown, the following steps are included:

[0087] S1: Preparation of nucleating agent component A

[0088] S1.1: Add 0.022 parts by mass of phthalic anhydride to a reaction flask, then add 30 parts by volume of THF. Stir magnetically at room temperature for 30 minutes until the phthalic anhydride is completely dissolved to obtain a phthalic anhydride THF solution.

[0089] S1.2: Take 0.01 parts by mass of aliphatic diamine and dissolve it in 20 parts by volume of THF to obtain an aliphatic diamine THF solution, and add the aliphatic diamine THF solution dropwise to the phthalic anhydride THF solution. The volume ratio of the aliphatic diamine THF solution to the phthalic anhydride THF solution is 3:1. After the addition is completed, the reaction is continued at room temperature for 24 hours, and the white precipitate is separated by centrifugation. The white precipitate is washed with THF 3 times, and the resulting product is vacuum dried at 80°C for 12 hours to obtain the nucleating agent component A.

[0090] S2: Preparation of nucleating agent component B

[0091] S2.1: Weigh lanthanum oxide and dissolve it in 37 wt% hydrochloric acid at a material-to-liquid ratio of 1:10. Heat in an oil bath at 100°C to obtain chloride crystals for later use.

[0092] S2.2: Dissolve the chloride crystals in ethanol to obtain a chloride-ethanol solution. The solid-liquid ratio of the chloride crystals to ethanol is 1:5 g / L. Stearic acid is then added to the chloride-ethanol solution and stirred to mix uniformly. The volume ratio of the chloride-ethanol solution to stearic acid is 1:3. Sodium hydroxide solution is then slowly added dropwise to adjust the pH to 8. The mixture is reacted in an oil bath at 95°C for 4 h to obtain a rare earth complex.

[0093] S2.3: Mix ethanol and distilled water in a volume ratio of 3:1 and add to a reaction flask. Stir magnetically for 30 minutes. Then, add calcium carbonate (10% by weight of the total mass of the system) to the reaction flask and allow it to completely disperse in the solution to obtain a calcium salt solution.

[0094] S2.4: Slowly add citric acid solution to calcium salt solution at 80°C and react for 40 minutes, then slowly add rare earth complex. The mass ratio of calcium salt solution, citric acid solution and rare earth complex is 10:2:5. Continue until the solution reacts to obtain a white emulsion. Dissolve it in alcohol under ultrasound until the white emulsion is completely dissolved. Finally, dry it at 100°C for 26 hours for use to obtain nucleating agent component B.

[0095] S3: Preparation of compound β nucleating agent

[0096] The nucleating agent component A and the nucleating agent component B are compounded in a volume ratio of 1:3 to obtain a compounded β-nucleating agent.

[0097] S4: Preparation of EVA composite VTES grafted EPDM

[0098] S4.1: Add 250 parts by mass of EPDM latex to a reaction flask and introduce nitrogen with stirring for 30 minutes. Heat the water bath to 72°C, add VTES and initiator BPO, and react under nitrogen for 6 hours. Rinse with distilled water and then vacuum dry at 50°C for 26 hours to obtain VTES-grafted EPDM.

[0099] S4.2: Weigh 2 parts by mass of EVA into a reaction flask, add 1 part by mass of DCP, and then add 3 parts by mass of acetone. Stir thoroughly until the materials in the reaction flask are evenly mixed. Place the reaction flask in a vacuum oven at room temperature to evacuate the acetone. After the acetone is completely evaporated, add 4 parts by mass of VTES-grafted EPDM. Add the mixture dropwise over 30 minutes and stir until evenly mixed.

[0100] S4.3: The contents of the reaction flask were then poured into a HAKKEE torque rheometer and melt grafted for 15 min at 210°C and 80 rpm. The mixture was then allowed to cool to room temperature to obtain a molten mixture.

[0101] S4.4: Crush the molten mixture and add xylene. The material-liquid ratio of the molten mixture to xylene is 1:25 g / mL. Stir at 80°C with the help of a magnetic stirrer until it is completely dissolved. While hot, drop the solution into a room temperature reaction bottle containing methanol. Stir while it precipitates. Filter to obtain the precipitate. Dry the precipitate in a blast oven to obtain EVA composite VTES grafted EPDM.

[0102] S5: Preparation of low temperature and high toughness PPR pipes

[0103] S5.1: Acrylic acid, HDPE, and benzophenone were mixed in a mass ratio of 4:6:0.1. After mixing, the mixture was irradiated with a UV lamp at 90°C for 2 hours. After the UV lamp irradiation was completed, the mixture was allowed to stand at room temperature for 5 hours.

[0104] S5.2: After the standing, 0.1 part of sodium persulfate is added to the acrylic acid and HDPE mixture, and the mixture is transferred to a twin-screw extruder for melt extrusion at 160°C, cooled, and pelletized to obtain acrylic acid-grafted HDPE;

[0105] S5.3: 80 parts by mass of PPR special resin, 2 parts by mass of acrylic grafted HDPE, 1 part by mass of EVA composite VTES grafted EPDM, 0.1 parts by mass of compound β-nucleating agent, 1 part by mass of silane coupling agent, 0.1 parts by mass of initiator BPO and 1 part by mass of masterbatch are placed in a blender and mixed for 10 minutes. The mixed raw materials are transferred to a twin-screw extruder for melt extrusion. The melting temperature of the raw materials is 210°C, the mold temperature is 220°C, the extrusion temperature is 200°C, the screw speed is 450r / min, the feeding frequency is 10r / min, and then cooled and shaped. The first stage of cooling and shaping is vacuum cooling with a vacuum degree of less than -0.06MPa and a cooling temperature of 50°C. The second stage of cooling and shaping is cooling under normal air pressure with a cooling temperature of 25°C. After cutting to a fixed length, a low-temperature and high-toughness PPR pipe is obtained.

[0106] Comparative Example 1:

[0107] Compared with Example 1, the difference of Comparative Example 1 is that in step S2, lanthanum oxide is not loaded on calcium carbonate, but directly used, specifically "S2: Preparation of nucleating agent component B

[0108] S2.1: Weigh lanthanum oxide and dissolve it in 37 wt% hydrochloric acid at a material-to-liquid ratio of 1:10. Heat in an oil bath at 90°C to obtain chloride crystals for later use.

[0109] S2.2: Dissolve the chloride crystals in ethanol to obtain a chloride-ethanol solution, wherein the solid-liquid ratio of the chloride crystals to ethanol is 1:5 g / L. Stearic acid is then added to the chloride-ethanol solution and stirred to uniformly mix, wherein the volume ratio of the chloride-ethanol solution to stearic acid is 1:3. Sodium hydroxide solution is then slowly added dropwise to adjust the pH to 8. The mixture is reacted in an 85°C oil bath for 3 h to obtain a rare earth complex, which is then dried at 90°C for 24 h for later use, thereby obtaining a nucleating agent component B. The resulting low-temperature, high-toughness PPR pipe is recorded as Comparative Example 1.

[0110] Comparative Example 2:

[0111] Compared with Example 1, the difference of Comparative Example 2 is that stearic acid is not added in step S2, specifically: "S2: Preparation of nucleating agent component B

[0112] S2.1: Weigh lanthanum oxide and dissolve it in 37 wt% hydrochloric acid at a material-to-liquid ratio of 1:10. Heat in an oil bath at 90°C to obtain chloride crystals for later use.

[0113] S2.2: Dissolve the chloride crystals in ethanol to obtain a chloride-ethanol solution at a solid-liquid ratio of 1:5 g / L. Slowly add sodium hydroxide solution dropwise to adjust the pH to 8. The mixture is reacted in an oil bath at 85°C for 3 h to obtain a rare earth complex.

[0114] S2.3: Mix ethanol and distilled water in a volume ratio of 3:1 and add to a reaction flask. Stir magnetically for 30 minutes. Then, add calcium carbonate (10% by weight of the total mass of the system) to the reaction flask and allow it to completely disperse in the solution to obtain a calcium salt solution.

[0115] S2.4: Slowly add citric acid solution to calcium salt solution at 80°C, react for 30 min, then slowly add rare earth complex (the mass ratio of calcium salt solution, citric acid solution, and rare earth complex is 10:2:5), and continue until the solution reacts completely to obtain a white emulsion. Dissolve the solution in alcohol under ultrasonication until the white emulsion is completely dissolved. Finally, dry the solution at 90°C for 24 h for later use, to obtain nucleating agent component B. The resulting low-temperature, high-toughness PPR pipe is designated as Comparative Example 2.

[0116] Comparative Example 3:

[0117] Compared with Example 1, the difference of Comparative Example 3 is that citric acid is not added in step S2, specifically: "S2: Preparation of nucleating agent component B

[0118] S2.1: Weigh lanthanum oxide and dissolve it in 37 wt% hydrochloric acid at a material-to-liquid ratio of 1:10. Heat in an oil bath at 90°C to obtain chloride crystals for later use.

[0119] S2.2: Dissolve the chloride crystals in ethanol to obtain a chloride-ethanol solution. The solid-liquid ratio of the chloride crystals to ethanol is 1:5 g / L. Stearic acid is then added to the chloride-ethanol solution and stirred to mix uniformly. The volume ratio of the chloride-ethanol solution to stearic acid is 1:3. Sodium hydroxide solution is then slowly added dropwise to adjust the pH to 8. The mixture is reacted in an oil bath at 85°C for 3 h to obtain a rare earth complex.

[0120] S2.3: Mix ethanol and distilled water in a volume ratio of 3:1 and add to a reaction flask. Stir magnetically for 30 minutes. Then, add calcium carbonate (10% by weight of the total mass of the system) to the reaction flask and allow it to completely disperse in the solution to obtain a calcium salt solution.

[0121] S2.4: Mix the calcium salt solution and the rare earth complex in a mass ratio of 10:5 until the solution reacts completely to obtain a white emulsion. Dissolve the mixture in alcohol under ultrasonication until the white emulsion is completely dissolved. Finally, dry the mixture at 90°C for 24 h for later use to obtain nucleating agent component B. The resulting low-temperature, high-toughness PPR pipe is designated as Comparative Example 3.

[0122] Comparative Example 4:

[0123] Compared with Example 1, the difference of Comparative Example 4 is that step S3 is not performed, and in step S5.3, the nucleating agent component A is used instead of the compound β-nucleating agent, specifically: "S5.3: 80 parts by mass of PPR special resin, 2 parts by mass of acrylic acid grafted HDPE, 1 part by mass of EVA composite VTES grafted EPDM, 0.1 part by mass of nucleating agent component A, 1 part by mass of silane coupling agent, 0.1 part by mass of initiator BPO and 1 part by mass of masterbatch are placed in a blender and mixed for 10 minutes, and the mixed raw materials are transferred to a stirring vessel. The twin-screw extruder performs melt extrusion, the melting temperature of the raw material is 190°C, the mold temperature is 190°C, the extrusion temperature is 180°C, the screw speed is 300r / min, the feeding frequency is 5r / min, and then cooling and shaping is performed. The first stage of cooling and shaping is vacuum cooling, the vacuum degree is less than -0.06MPa, and the cooling temperature is 30°C. The second stage of cooling and shaping is cooling under normal pressure, and the cooling temperature is 15°C. After fixed length cutting, a low-temperature high-toughness PPR pipe is obtained. The obtained low-temperature high-toughness PPR pipe is recorded as Comparative Example 4.

[0124] Comparative Example 5:

[0125] Compared with Example 1, the difference of Comparative Example 5 is that step S3 is not performed, and in step S5.3, the compound β-nucleating agent is replaced by the nucleating agent component B, specifically: "S5.31: 80 parts by mass of PPR special resin, 2 parts by mass of acrylic acid grafted HDPE, 1 part by mass of EVA composite VTES grafted EPDM, 0.1 part by mass of nucleating agent component B, 1 part by mass of silane coupling agent, 0.1 part by mass of initiator BPO and 1 part by mass of masterbatch are placed in a blender and mixed for 10 minutes, and the mixed raw materials are converted into The raw material was melt-extruded into a twin-screw extruder, the melting temperature of the raw material was 190°C, the mold temperature was 190°C, the extrusion temperature was 180°C, the screw speed was 300r / min, and the feeding frequency was 5r / min. The raw material was then cooled and shaped. The first stage of cooling and shaping was vacuum cooling, the vacuum degree was less than -0.06MPa, and the cooling temperature was 30°C. The second stage of cooling and shaping was cooling under normal pressure, and the cooling temperature was 15°C. After cutting to a fixed length, a low-temperature high-toughness PPR pipe was obtained. The obtained low-temperature high-toughness PPR pipe was recorded as Comparative Example 5.

[0126] Comparative Example 6:

[0127] Compared with Example 1, the difference of Comparative Example 6 is that Step S5.1 and Step S5.2 are not performed, and in Step S5.3, PVC of equal mass is used instead of acrylic acid grafted HDPE, specifically: "S5: Preparation of low-temperature high-toughness PPR pipe

[0128] S5.3: 80 parts by mass of PPR special resin, 2 parts by mass of PVC, 1 part by mass of EVA composite VTES grafted EPDM, 0.1 part by mass of compound β-nucleating agent, 1 part by mass of silane coupling agent, 0.1 part by mass of initiator BPO and 1 part by mass of masterbatch were placed in a blender and mixed for 10 minutes. The mixed raw materials were transferred to a twin-screw extruder for melt extrusion. The melting temperature of the raw materials was 190°C, the mold temperature was 190°C, the extrusion temperature was 180°C, the screw speed was 300 r / min, and the feeding frequency was 5 r / min. The pipe was then cooled and shaped. The first stage of cooling and shaping was vacuum cooling with a vacuum degree of less than -0.06 MPa and a cooling temperature of 30°C. The second stage of cooling and shaping was cooling under normal air pressure with a cooling temperature of 15°C. The pipe was cut to a fixed length to obtain a low-temperature high-toughness PPR pipe. The obtained low-temperature high-toughness PPR pipe was recorded as Comparative Example 6.

[0129] The performance tests of the low-temperature high-toughness PPR pipes prepared in Examples 1-3 and Comparative Examples 1-6 were performed respectively. The test contents and standards are as follows:

[0130] (1) Low-temperature drop hammer impact: The samples were subjected to a drop hammer impact test using a drop hammer tester with a hammer weight of 1 kg and a drop height of 1 m. 100 samples were placed at -18°C for 24 h. Each sample completed the drop hammer impact test within 15 s, and the number of samples that broke was recorded.

[0131] (2) β-crystal crystallinity test: XRD tests were performed on appropriate bulk samples cut from the sample pipe. The β-crystal crystallinity in the PPR pipe was calculated using the XRD data. The XRD test used a Cu-Ka target, with an X-ray wavelength of 0.154 nm, a scanning voltage of 40 kV and a scanning current of 40 mA, a scanning range of θ = 5-30°, and a scanning speed of 5° / min.

[0132] (3) Hydrostatic test: The test is carried out in accordance with GB / T6111-2003 standard, and the rupture and leakage of PPR pipes are tested at 20°C, environmental stress 16 MPa, and time 1 hour.

[0133] Table 1: Low temperature drop hammer test

[0134] Number of broken samples Example 1 5 Example 2 7 Example 3 6 Comparative Example 1 42 Comparative Example 2 35 Comparative Example 3 34 Comparative Example 4 61 Comparative Example 5 53 Comparative Example 6 37

[0135] Table 2: β-crystallinity

[0136] β crystallinity (%) Example 1 59.95 Example 2 58.43 Example 3 59.62 Comparative Example 1 40.29 Comparative Example 2 42.46 Comparative Example 3 45.31 Comparative Example 4 30.26 Comparative Example 5 34.98 Comparative Example 6 48.73

[0137] Table 3: Hydrostatic test

[0138] Rupture and leakage Example 1 No rupture, no leakage Example 2 No cracks, no leakage Example 3 No rupture, no leakage Comparative Example 1 0.9h rupture, 0.8h leakage Comparative Example 2 No cracks, no leakage Comparative Example 3 No cracks, no leakage Comparative Example 4 0.8h rupture, 0.7h leakage Comparative Example 5 0.8h rupture, 0.7h leakage Comparative Example 6 0.9h rupture, 0.7h leakage

[0139] The β-crystal crystallinity of Examples 1-3 is 59.95%, 58.43%, and 59.62%, respectively, and the highest number of sample breakage is 7. Pipes with β-crystal crystallinity will exhibit better mechanical strength when subjected to external force. Therefore, from the fact that the β-crystal crystallinity of Examples 1-3 is higher than that of the comparative example, it can be seen that the pipes of the examples have better toughness. Moreover, in the low-temperature drop hammer test, the number of sample breakages of the examples is also much lower than that of the comparative example. It can be seen that the examples also have good toughness in a low-temperature environment and are not easy to break.

[0140] The number of sample breakages in Comparative Example 1 is 42, and the β-crystal crystallinity is 40.29%. The high number of sample breakages indicates that the physical strength of Comparative Example 1 is low under low temperature conditions. From the fact that the β-crystal crystallinity of Comparative Example 1 is lower than that of the embodiment, it can also be seen that the toughness of the pipe of Comparative Example 1 is lower than that of the embodiment. At the same time, Comparative Example 1 broke at 0.9h and leaked at 0.8h in the hydrostatic test at 20°C, indicating that the pressure resistance of Comparative Example 1 is poor. This is because there is no calcium carbonate to load lanthanum oxide, and the surface morphology of lanthanum oxide cannot be changed. Therefore, the dispersion of lanthanum oxide in the polymer matrix is ​​insufficient, and the rigidity and low-temperature toughness of the pipe are greatly reduced.

[0141] The number of sample breakages in Comparative Example 2 is 35, and the β-crystal crystallinity is 42.46%. The number of sample breakages is smaller than that in Comparative Example 1, but still much larger than that in the embodiment. Its physical strength in a low-temperature environment is worse than that in the embodiment, but better than that in Comparative Example 1, and the β-crystal crystallinity is also higher than that in Comparative Example 1. It can be seen that the toughness of the pipe in Comparative Example 2 is worse than that in Comparative Example 1, but both are inferior to the embodiment. The lubrication between the particles of the calcium carbonate-loaded lanthanum oxide system without the addition of stearic acid is reduced, and the interfacial bonding force between calcium carbonate and lanthanum oxide is reduced. Therefore, although the calcium carbonate-loaded lanthanum oxide plays the role of a nucleating agent, the calcium carbonate and lanthanum oxide are separated in the later stage of the reaction, and the dispersion of the nucleating agent particles is reduced, resulting in a decrease in the mechanical strength of the pipe.

[0142] The β-crystal crystallinity of Comparative Example 3 is 45.31%, which shows that the toughness of the pipe of Comparative Example 3 at room temperature is the best among Examples 1-3. The number of sample breakages is 34, indicating that the low-temperature toughness of the pipe is not much different from that of Comparative Example 2. Compared with the examples, both have a decrease in toughness at low temperatures. It can be seen that citric acid also plays a role in improving the stability of calcium carbonate-loaded lanthanum oxide at low temperatures.

[0143] The β-crystal crystallinity of Comparative Example 4 is 30.26%, and the β-crystal crystallinity of Comparative Example 5 is 34.98%. The effect of a single nucleating agent is worse than that of a compound nucleating agent, and the crystallinity of both decreases. The number of broken samples in Comparative Example 4 is 61, and the number of broken samples in Comparative Example 5 is 53. It can be seen that due to the decrease in crystallinity, the toughness at low temperatures is also affected and further decreases. In addition, cracks and leakage occurred in the hydrostatic tests of Comparative Examples 4 and 5, which also shows that the compressive performance of Comparative Examples 4 and 5 is poor.

[0144] The β-crystal crystallinity of Comparative Example 6 is 48.73%, which is lower than that of Examples 1-3, but higher than that of Comparative Examples 1-5. This shows that the pipe of Comparative Example 6 has certain desirable physical strength at room temperature. However, the number of sample breakages in Comparative Example 6 is 37, indicating that its toughness in a low-temperature environment is far inferior to that of the examples. In the hydrostatic test, rupture occurs at 0.9 h and leakage occurs at 0.7 h, indicating that its compressive resistance is also inferior to that of the examples. It can be seen that acrylic acid-grafted HDPE has better physical strength, impact resistance and toughness at low temperatures than PPR pipes made of other conventional materials.

[0145] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A preparation process for a modified low-temperature high-toughness PPR pipe, characterized in that: The steps include: S1: Preparation of nucleating agent component A Dissolving phthalic anhydride in THF to obtain a phthalic anhydride THF solution, dissolving an aliphatic diamine in THF to obtain an aliphatic diamine THF solution, and adding the aliphatic diamine THF solution dropwise to the phthalic anhydride THF solution to react and obtain a nucleating agent component A; S2: Preparation of nucleating agent component B Weigh lanthanum oxide and dissolve it in hydrochloric acid to obtain chloride crystals, dissolve the chloride crystals in ethanol to obtain a chloride ethanol solution, add stearic acid to the chloride ethanol solution to react to obtain a rare earth complex, mix alcohol and distilled water, add calcium carbonate to obtain a calcium salt solution, and react the calcium salt solution, citric acid solution and rare earth complex to prepare a nucleating agent component B; S3: Preparation of compound β-nucleating agent The nucleating agent component A and the nucleating agent component B are compounded in a volume ratio of 1:(2-3) to obtain a compounded β-nucleating agent; S4: Preparation of EVA composite VTES grafted EPDM Add EPDM latex into a reaction bottle, then add VTES and initiator BPO to obtain VTES-grafted EPDM, put EVA into the reaction bottle, then add DCP and acetone, stir well and remove acetone, then add VTES-grafted EPDM to prepare a molten mixture, purify the molten mixture to obtain EVA composite VTES-grafted EPDM; S5: Preparation of low temperature and high toughness PPR pipe Acrylic acid, HDPE and benzophenone are reacted and sodium persulfate is added, and melt extruded to obtain acrylic acid grafted HDPE. PPR special resin, acrylic acid grafted HDPE, EVA composite VTES grafted EPDM, compounded β nucleating agent, silane coupling agent, initiator BPO and masterbatch are mixed and stirred, and the mixed raw materials are melt-extruded, cooled and shaped, and cut to a fixed length to obtain a low-temperature and high-toughness PPR pipe.

2. The preparation process of a modified low-temperature high-toughness PPR pipe according to claim 1 is characterized in that: Step S1: preparing a nucleating agent component A, comprising the following steps: S1.1: Add 0.022-0.045 parts by mass of phthalic anhydride to a reaction flask, then add 30-35 parts by volume of THF, and stir magnetically at room temperature for 30-40 minutes until the phthalic anhydride is completely dissolved to obtain a phthalic anhydride THF solution; S1.2: Take 0.01-0.05 parts by mass of aliphatic diamine and dissolve it in 20-30 parts by volume of THF to obtain an aliphatic diamine THF solution, and add the aliphatic diamine THF solution dropwise to the phthalic anhydride THF solution. The volume ratio of the aliphatic diamine THF solution to the phthalic anhydride THF solution is 3:

1. After the addition is completed, continue to react at room temperature for 24-26 hours, separate the white precipitate by centrifugation, wash the white precipitate with THF for 3-5 times, and vacuum dry the resulting product at 60-80°C for 12-14 hours to obtain nucleating agent component A.

3. The preparation process of a modified low-temperature high-toughness PPR pipe according to claim 1 is characterized in that: Step S2: preparing nucleating agent component B, comprising the following steps: S2.1: Weigh lanthanum oxide and dissolve it in 37wt% hydrochloric acid, the material-liquid ratio of lanthanum oxide to hydrochloric acid is 1:(9-10), heat in an oil bath at 90-100°C, and finally obtain chloride crystals for later use; S2.2: dissolving chloride crystals in ethanol, the solid-liquid ratio of chloride crystals to ethanol is 1:(5-6) g / L, to obtain a chloride ethanol solution, then adding stearic acid to the chloride ethanol solution and stirring to make it uniformly mixed, the volume ratio of chloride ethanol solution to stearic acid is 1:(3-5), then slowly adding sodium hydroxide solution to adjust the pH value to 8, reacting in an oil bath at 85-95°C for 3-4 hours, to obtain a rare earth complex; S2.3: alcohol and distilled water are mixed in a volume ratio of (3-5):1, and added to a reaction bottle, and magnetically stirred for 30-40 minutes, and then 10-15% of the total mass of calcium carbonate in the reaction bottle is added to completely disperse it in the solution to obtain a calcium salt solution; S2.4: Slowly add citric acid solution to calcium salt solution at 80-90℃ and react for 30-40min, then slowly add rare earth complex, the mass ratio of calcium salt solution, citric acid solution and rare earth complex is (10-15):2:5, until the solution reacts completely to obtain a white emulsion, dissolve it in alcohol under ultrasound until the white emulsion is completely dissolved, and finally dry it at 90-100℃ for 24-26h for use, to obtain nucleating agent component B.

4. The preparation process of a modified low-temperature high-toughness PPR pipe according to claim 1 is characterized in that: Step S4 prepares EVA composite VTES grafted EPDM, comprising the following steps: S4.1: Add 250-300 parts by weight of EPDM latex to a reaction bottle, introduce nitrogen for 30 minutes while stirring, heat the water bath to 68-72°C, add VTES and initiator BPO, react for 6-8 hours under nitrogen protection, rinse with distilled water, and then vacuum dry at 40-50°C to remove water for 24-26 hours to obtain VTES-grafted EPDM; S4.2: Weigh 2-3 parts by mass of EVA and put it into a reaction bottle, then add 1-1.5 parts by mass of DCP, and then add 3-4 parts by mass of acetone, stir thoroughly until the materials in the reaction bottle are evenly mixed, place it in a vacuum oven at room temperature to evacuate to remove the acetone, and after the acetone is completely volatilized, add 4-5 parts by mass of VTES-grafted EPDM, and add it dropwise within 30 minutes, and stir evenly; S4.3: Then pour the material in the reaction bottle into the HAKKEE torque rheometer, melt-graft for 10-15 minutes at 170-210°C and a rotation speed of 60-80 r / min, and cool to room temperature to obtain a molten mixture; S4.4: Crush the molten mixture, add xylene, the solid-liquid ratio of the molten mixture to xylene is 1: (25-30) g / mL, stir at 60-80°C with the help of a magnetic stirrer until it is completely dissolved, drop the solution into a room temperature reaction bottle containing methanol while it is still hot, stir while precipitating, filter to obtain the precipitate, and dry the precipitate in a forced air oven to obtain EVA composite VTES grafted EPDM.

5. The preparation process of a modified low-temperature high-toughness PPR pipe according to claim 1 is characterized in that: Step S5 prepares low-temperature high-toughness PPR pipes, including the following steps: S5.1: acrylic acid, HDPE and benzophenone are mixed in a mass ratio of (4-8): (6-10): (0.1-2), and after mixing, irradiated with ultraviolet light at a temperature of 80-90° C. for 1-2 hours, and then allowed to stand at room temperature for 3-5 hours after the ultraviolet light irradiation is completed; S5.2: After the standing, 0.1-2 parts of sodium persulfate are added to the mixture of acrylic acid and HDPE, and the mixture is transferred into a twin-screw extruder for melt extrusion at 160-210° C., cooled, and pelletized to obtain acrylic acid grafted HDPE; S5.3: Place 80-90 parts by mass of PPR special resin, 2-4 parts by mass of acrylic grafted HDPE, 1-5 parts by mass of EVA composite VTES grafted EPDM, 0.1-2 parts by mass of compounded β-nucleating agent, 1-3 parts by mass of silane coupling agent, 0.1-1 parts by mass of initiator BPO and 1-3 parts by mass of masterbatch into a blender and mix and stir for 10-15 minutes. Transfer the mixed raw materials to a twin-screw extruder for melt extrusion. After cooling, shaping and fixed-length cutting, a low-temperature and high-toughness PPR pipe is obtained.

6. The preparation process of a modified low-temperature high-toughness PPR pipe according to claim 5 is characterized in that: The melting temperature of the raw materials is 190-210°C, the mold temperature is 190-220°C, the extrusion temperature is 180-200°C, the screw speed is 300-450r / min, the feeding frequency is 5-10r / min, the first stage of cooling and shaping is vacuum cooling, the vacuum degree is less than -0.06MPa, the cooling temperature is 30-50°C, and the second stage of cooling and shaping is cooling under normal air pressure, and the cooling temperature is 15-25°C.

7. A modified low-temperature high-toughness PPR pipe, which is prepared by the preparation process of the modified low-temperature high-toughness PPR pipe according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • A low-temperature crack-resistant PPR pipe with controllable crystal structure and its preparation method

    CN104592644B

  • A PPR pipe material resistant to low-temperature cracking, its preparation method, and the resulting PPR pipe products.

    CN113061304B

Cited By

  • PP-R cold and hot water pipe and preparation method thereof

    CN119931217A